39-7x=4(7x*7)+4

Simple and best practice solution for 39-7x=4(7x*7)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-7x=4(7x*7)+4 equation:



39-7x=4(7x*7)+4
We move all terms to the left:
39-7x-(4(7x*7)+4)=0
We add all the numbers together, and all the variables
-7x-(4(+7x*7)+4)+39=0
We calculate terms in parentheses: -(4(+7x*7)+4), so:
4(+7x*7)+4
We multiply parentheses
196x+4
Back to the equation:
-(196x+4)
We get rid of parentheses
-7x-196x-4+39=0
We add all the numbers together, and all the variables
-203x+35=0
We move all terms containing x to the left, all other terms to the right
-203x=-35
x=-35/-203
x=5/29

See similar equations:

| -9+x-4)=81 | | 4x+7=x-28 | | 0.25x=-11 | | 40/w=10 | | -3x+4=x+8 | | -2u^2-3u+14=0 | | 2x-3|7=3x-5|10 | | 300x-0.49=500x+0.15 | | (x^2-148x+5476)(x+29)=0 | | x/4=x-6/5 | | 6x-9=-3x+63 | | 4(x+5)=150 | | 2(5y+6)-3=4y+2 | | -0.55=0.2(x-61/2) | | (5b*2)+(4b*2)=72 | | 8x+12=108+6x | | a/74=6.79 | | 15=3v-15 | | y2+12y=–7 | | −v−4=3v | | 5v+12=13 | | 5v2+12v=13 | | 3x+21=123 | | 3x+14=4x-26 | | 12(9x+3)=1008 | | 6.3r=45.36 | | 85z​ −18=824−2z​ | | a+21=-9 | | 8(2^x*3)=48 | | 14=-8m | | z+45=33 | | 7x=30-2 |

Equations solver categories